Cytological features of the bulbar conjunctiva in patients with type 2 diabetes mellitus (Ukrainian Journal of Ophthalmology, 2025)
Background: Pathologic changes in the ocular surface in diabetes mellitus (DM) may result from various causes such as metabolic abnormalities (hyperglycemia and dyslipidemia, leading to changes in tear composition), perilimbal vascular microangiopathy (leading to impaired blood supply to the cornea), lacrimal gland lesions, and various abnormalities in innervation.Purpose: To determine the cytological features of the bulbar conjunctival epithelium in patients with T2DM.Material and Methods: We analyzed clinical and impressive cytology data of 34 patients (18 (52.9%) men and 16 (47.1%) women; age, 50 to 79 years) having clinical signs of dry eye disease (DED). Patients were divided into two equal groups of 17 patients each, group 1 (diabetes duration of less than 5 years) and group 2 (diabetes duration of more than 5 years). They underwent Schirmer 1 test, tear break-up time (TBUT) test, and impression cytology of the bulbar conjunctiva. The cytologic changes of the bulbar conjunctiva were graded according to Nelson’s grading system.Results: Comparison of clinical and cytolological characteristics of study patients suggests that, severity, duration and course pattern of diabetes mellitus affect the development of compensatory and adaptive mechanisms in the bulbar conjunctival epithelium, these mechanisms being reflected by the formation of the surface epithelium of increased density due to squamous metaplasia and keratinization.Conclusion: Our impression cytology study of the bulbar conjunctival epithelium found that most patients (94.1%) with T2DM had squamous metaplasia grade (Nelson) of 2 or 3, and 80% of those with squamous metaplasia grade (Nelson) of 3 had T2DM duration of more than 5 years. In addition, squamous metaplasia of grade 3 was fourfold more common among patients with T2DM duration of more than 5 years than among those with T2DM duration of less than 5 years.
Keywords: impression cytology; bulbar conjunctiva; type 2 diabetes mellitus